Are Bivocational Clergy Becoming the New Normal?: An Analysis of the Current Population Survey, 1996-2017 - Perry, Samuel L. (Journal for the scientific study of religion, 2019)
Transitions in the American religious landscape including religious nonaffiliation, congregational and seminary enrollment declines, and the proliferation of megachurches have reshaped the clergy labor market and increased the precariousness of this type of work. One potential indication of this growing instability is the supposedly increasing number of bivocational clergy who depend on a second job to supplement their income. There are few reliable data, however, that can trace out national-level trends of bivocational clergy. Using the Current Population Survey, this study tests whether there has been any proportional increase in bivocational clergy and to what extent such an increase has been localized to certain groups. We find that the percentage of clergy who report having a second job has not increased since 1996. However, clergy who are female, unmarried, or working in the American northeast are increasingly likely to report working a second job. These trends suggest that clergy who receive occupational advantages-due to gender or marital status-or who live in highly religious/low cost-of-living regions of the country may be protected from taking on a second job whereas those clergy without these advantages increasingly must depend on additional sources of income.